Protein supplementation for cows wintered on milo stubble - McKee, M.; Kimole, K.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
Cows in mid-to-late gestation gained significantly (P<.05) more while grazing milo stover supplemented on alternative days with 4 lbs. per head of a natural protein than cows with no protein supplement. Although protein supplementation stimulated extra gain, the cows receiving no protein supplement gained weight and maintained adequate condition for mid-to-late gestation. When quality and quantity of milo stover are satisfactory, satisfactory performance can be achieved by cows in mid-to-late gestation without supplemental protein.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Protein; Milo stubble; Milo stover